Infant Young Child Feeding Practices From 12 to 24 Months of Age of Offspring From the Women First Trial. (7th June 2021) - Long, Julie; Gatica-Domínguez, Giovanna; Westcott, Jamie; Tejeda, Gabriela; Diba, Tshilenge; Mastiholi, Shivanand; Khan, Umber; Garcés, Ana; Figueroa, Lester; Lokangaka, Adrien; Goudar, Shivaprasad; Ali, Sumera; et al.
Abstract: Objectives: Evaluate infant young child feeding (IYCF) trends from 12 to 24 mo in four low middle-income countries: Democratic Republic of Congo (DRC); Guatemala; India; and Pakistan. Methods: 2413 children (570 DRC, 614 Guatemala, 589 India, and 640 Pakistan) born to women from the Women First Trial enrolled. Trained research health workers visited households and assessed children's feeding practices from 12 to 24 mo. Child feeding indicators including the prevalence and longitudinal trends of meeting minimum diet diversity (MDD), minimum meal frequency (MMF), and minimum acceptable diet (MAD) were analyzed using the 2018 IYCF definitions from 12 to 24 mo for all four sites individually and combined. Results: MDD significantly increased from 16% at 12 mo to 29% at 24 mo for all sites combined (p < 0.001); by site: 3 to 10 for DRC (p < 0.001), 33 to 42 for Guatemala (p = 0.001), 28 to 63 for India (p < 0.001), and 1 to 2 for Pakistan (not significant). MMF significantly increased from 49% at 12 mo to 68% at 24 mo for all sites (p < 0.001); by site: 22 to 49 for DRC (p < 0.001), 89 to 92 for Guatemala (not significant), 66 to 73 for India (0.012), and 18 to 58 for Pakistan (p < 0.001). MAD significantly increased (p < 0.001) for all sites, and by site for DRC and India only. Food groups least consumed at 24 mo for all sites were nuts/pulses (prevalence 20%), meats/fish/insects (21%), and vitamin A rich fruits & vegetables (38%); compared to grains/roots/tubers which were consumed by 98% of participants. For all sites, milk & dairy and eggs consumption significantly increased from 50 to 60% (p < 0.001) and 26 to 50% (p < 0.001), respectively. Breastfeeding decreased from 94% at 12 mo to 49% at 24 mo for all sites with the lowest prevalence of breastfeeding in Pakistan (23%), whereas the other sites were ∼50%. Conclusions: For all sites, the prevalence of participants meeting IYCF recommendations for feeding indicators increased from 12 to 24 mo, but prevalence at 24 mo remained well below recommendations in all sites. Children with low IYCF scores are at risk for low intakes of vital nutrients, protein and vitamin A rich foods, which may negatively impact periods of rapid growth and development in these resource limited populations. Funding Sources: Bill & Melinda Gates Foundation and Eunice Kennedy Shriver NICHD.